2023
DOI: 10.3390/microorganisms11092343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Stages and Lactic Acid Fermentation on Anti-Nutrients and Nutritional Attributes of Spinach (Spinacia oleracea)

Adila Naseem,
Saeed Akhtar,
Tariq Ismail
et al.

Abstract: Spinach (Spinacia oleracea) is a winter-season green, leafy vegetable grown all over the world, belonging to the family Amaranthus, sub-family Chenopodiaceae. Spinach is a low-caloric food and an enormous source of micronutrients, e.g., calcium, folates, zinc, retinol, iron, ascorbic acid and magnesium. Contrarily, it also contains a variety of anti-nutritional factors, e.g., alkaloids, phytates, saponins, oxalates, tannins and many other natural toxicants which may hinder nutrient-absorption. This study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
2
1
0
Order By: Relevance
“…Fermentation treatment increased the ash, protein and fiber contents, whereas moisture, fat and carbohydrate contents decreased among B. campestris samples, and the trend was similar for all three stages. In addition, the results of the present investigation agree with previous findings of [ 54 , 55 , 56 ]. A continued fermentation for a long time may result in decreased fat content that could be attributed to lipolytic activities and the utilization of lipids as an energy source by the fermenting microorganisms [ 57 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Fermentation treatment increased the ash, protein and fiber contents, whereas moisture, fat and carbohydrate contents decreased among B. campestris samples, and the trend was similar for all three stages. In addition, the results of the present investigation agree with previous findings of [ 54 , 55 , 56 ]. A continued fermentation for a long time may result in decreased fat content that could be attributed to lipolytic activities and the utilization of lipids as an energy source by the fermenting microorganisms [ 57 ].…”
Section: Discussionsupporting
confidence: 93%
“…Results of the present investigation ( Table 5 ) showed that blanching causes a decrease in total phenolic and flavonoids, whereas fermentation causes the opposite. Our results agree with results obtained by other researchers who found that fermentation leads to a slight increase in phytochemical contents [ 55 , 61 ]. Our findings indicated that the ethanol, n -hexane and methanol extracts have higher flavonoid concentrations in B. campestris as compared to the total flavonoid content (TFC) in the various vegetable samples ranging from 1.09 to 3.59 mg CE/g.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation